Value Congruence and Organizational Commitment: Does Work Happiness Matter? - Oyelakin, Oyekunle; Shodeinde , Adekunle D.; Arandong, Idi Jamok (Business Perspective Review, 2022)
Purpose: Lack of employee commitment to their organization has been reported as one of the numerous challenges faced by the Nigerian Civil Service. The study investigated the mediating role of work happiness on the relationship between value congruence and organizational commitment in Federal Public Service in Abuja, Nigeria. Method: Data were collected from the Nigerian Civil Service staff in Abuja, Nigeria. Following the random sampling technique, a total of 386 responses were used for data analysis. Data were analyzed using SmartPLS 3. Results: Findings revealed that value congruence and work happiness have a positive and significant effect on organizational commitment. Work happiness is also found to have fully mediated the relationship between value congruence and organizational commitment. Implication: The study implies that value congruence and work happiness are factors to be considered in getting employees committed to organizational goals and objectives. It also recommends that regulatory authority should ensure a congenial environment for the staff of Federal Civil Service that would make them happy and committed to the organization.